PENINGKATAN PENGETAHUAN IBU DALAM MENSTIMULASI PERKEMBANGAN MOTORIK HALUS PADA ANAK MELALUI MEDIA SMART PHONE - Rukmini, Rukmini; Sholihah, Wardatus; Andriani, Dewi (Community Development in Health Journal, 2025)
ABSTRACT Introduction & Aim: Children's fine motor skill development is crucial since it directly affects their ability to do daily tasks and participate in other academic pursuits. It is anticipated that parents will be able to use smartphone media to encourage the development of preschool-aged children's fine motor abilities. This activity aims to increase parental knowledge in stimulating children's fine motor development using smartphone media. Method of Activity: Community service were given to 30 parents at TK Tunas Harapan. This four-week community service project involved multiple stages of action, including an initial survey, education, application, demonstration and redemonstration, also assessment, and it was conductedat Jalan Kedung Mangu No.80, Sidotopo Wetan, Kec. Kenjeran, Surabaya. Data were examined statistically using the Wilcoxon signed rank test. Results: The results of the Wilcoxon Signed Ranks test showed a significant change in parental knowledge with a p-value of 0.000. Discussion: Providing education to parents about children's fine motor development using smartphone media is a choice to enhance parents' knowledge in stimulating children's fine motor development, be accompanied by supervision and wise time management. Keywords: Fine Motor, Education, Smart Phone